The roots of a quadratic equation ax^2 + bx + c = 0 are given by x1 = [-b + sqrt (b^2 – 4ac)]/2a and x2 = [-b - sqrt (b^2 – 4ac)]/2a.

If the two roots are to be equal, sqrt (b^2 – 4ac) should be equal to 0

=> sqrt (b^2 – 4*18*4) = 0

=> b^2 – 4*18*4 = 0

=> b^2 = 4*18*4

=> b = + sqrt (4*18*4) and b = -sqrt (4*18*4)

=> b = 12*sqrt 2 and b = -12*sqrt 2

**Therefore b can be equal to 12*sqrt 2 and -12*sqrt 2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now